Association of Physician Specialty with Hospice Referral for Hospitalized Nursing Home Patients with Advanced Dementia. Issue 8 (28th March 2017) - Ankuda, Claire K.; Mitchell, Susan L.; Gozalo, Pedro; Mor, Vince; Meltzer, David; Teno, Joan M.
Abstract : Objectives: Hospitalists hospice referral patterns have been unstudied. This study aims to examine hospice referral rates by attending type for hospitalized nursing home (NH) residents with advanced cognitive impairment (ACI) at the time of discharge between 2000 and 2010. Design: Retrospective cohort study. Participants: Hospitalized NH residents age ≥66 drawn from the 20% sample of Medicare beneficiaries with ACI, 4 or more activities of daily living (ADL) impairments on last minimum data set (MDS) assessment completed within 120 days of admission (n = 128, 989). Measurements: Hospice referral was defined as referral to hospice within 1 day after hospital discharge. Attending physician type was determined by Part B physician billing for 100% of the billings during that admission. Continuity of care was defined as the hospital physician also billing for an outpatient visit within 120 days of that hospital admission. Number of ADL impairments, cognitive measures, pre‐admission illnesses and illness severity were derived from the MDS. Results: Of the 105, 329 hospitalized patients with ACI that survived to discharge (72.3% white, 30.6% male), the hospice referral rate at the time of hospital discharge increased from 2.8% in 2000 to 11.2% in 2010. Using a multivariate, hospital fixed effects model examining changes in the distribution of inpatient attending physicians, hospitalists compared to generalist physicians were more likely to refer these patients to hospice at discharge (AOR 1.17, 95% CI 1.09–1.26). Continuity of physician care from the outpatient setting to the hospital was associated with lower hospice referral (AOR 0.78, 95% CI 0.73–0.85). Conclusion: Hospice referrals for NH‐dwelling persons with ACI admitted to the hospital increased between 2000 and 2011 and disproportionately so when the attending physician was a hospitalist.